Digital Social Networks and Urban Spaces - Florentino, Pablo Vieira; Furtado Rocha, Maria Célia; Corso Pereira, Gilberto (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The goal of this paper is to explore how available data from digital social networks can be used to understand ongoing collective actions on urban micro spaces. For this we analyze two cases, one in Brazil and the other in Italy. We propose to conduct an exploratory exercise about group discussions in digital social networks interactions on issues that affect the use of residual public spaces as a way to understand how collective actions are trying to modify  urban environment. Aiming to verify the possibilities of analysis of this kind of interaction we made a study of digital urban movements in two cities: Salvador (Brazil) and Potenza (Italy). Such study aims to perform social networks analysis from groups and interactions on digital communities. This permits to test specific research methods to understand how groups and individuals are articulated for qualify cities micro environments, by using digital social networks platforms as a way to improve public participation in a broad sense.